2020
DOI: 10.4212/cjhp.v73i2.2977
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance des substances contrôlées en établissements de santé : une contribution à la gestion de la crise des opioïdes au Canada

Abstract: RÉSUMÉContexte : La consommation des substances contrôlées et plus particulièrement des opioïdes est un enjeu de santé publique. Le Canada se situe au deuxième rang des plus gros consommateurs d’opioïdes dans le monde. L’utilisation de ces substances est associée à des problèmes de mésusage. À preuve, une crise des opioïdes sévit en Amérique du Nord.Objectifs : Décrire et analyser les tendances de consommation des substances contrôlées au sein d’un établissement de santé de 2003-2004 à 2017-2018. Proposer un o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, pain can be difficult to measure. The pharmacist's role in pain management is expanding, as evidenced by the study on opioid controls reported by Videau and others, 7 the comparison of topical amitriptyline formulas to improve clinical efficacy in neuropathic pain reported by Shakshuki and others, 8 , and the investigation of methadone stability by Friciu and others. 9 These papers all provide evidence on how to improve the safety and efficacy of pain medicines, and they all reflect work to ensure that medicines do their work without hurting the patient.…”
Section: Rebekah Molesmentioning
confidence: 99%
“…In addition, pain can be difficult to measure. The pharmacist's role in pain management is expanding, as evidenced by the study on opioid controls reported by Videau and others, 7 the comparison of topical amitriptyline formulas to improve clinical efficacy in neuropathic pain reported by Shakshuki and others, 8 , and the investigation of methadone stability by Friciu and others. 9 These papers all provide evidence on how to improve the safety and efficacy of pain medicines, and they all reflect work to ensure that medicines do their work without hurting the patient.…”
Section: Rebekah Molesmentioning
confidence: 99%